The Relation Of Physical Activity and Grade of Hypertension in Eldelry Prolanis Participants in Ngawen II Public Health Center Gunungkidul: Hubungan Aktivitas Fisik Dengan Derajat Hipertensi Pada Lansia Peserta Prolanis Di Puskesmas Ngawen II Kabupaten Gunungkidul - Antonius Yoga Setiyawan; Mahayanti, Agnes; Widianti, Christina Ririn Widiant (LPPM STIKES Guna Bangsa, 2024)
Hypertension is one of non-communicable diseases (NCDs) that cause the most mortalities in the world. Hypertension is an incurable disease with high risk of complications. Regular physical activity is one way to reduce the risk of complications. This research aims to determine the relationship between physical activity and the degree of hypertension in elderly prolanis participants at the Ngawen II Gunungkidul Health Center. Quantitative research design with descriptive correlation type with cross sectional approach. The study population was all elderly people with hypertension participating in prolanis at the Ngawen II Gunungkidul Health Center, totaling 150 people. The sample was 50 people, taken by accidental sampling technique. The instrument used is the Physical Activities Scale for Elderly (PASE) questionnaire, data analysis using the Spearman correlation test. The results showed that the portrait of physical activity of elderly people with hypertension participating in prolanis 39 respondents (78%) had a moderate level of physical activity, 6 respondents (12%) had a good level of physical activity and 5 respondents (10%) had a poor level of physical activity. The description of the degree of hypertension of elderly prolanis participants was 29 respondents (58%) mild category hypertension, 15 respondents (30%) moderate category hypertension, and 6 respondents (12%) severe category hypertension. Spearman correlation test show that there is a significant relationship between physical activity and the degree of hypertension in elderly hypertensive patients with prolanis participants. Researchers recommend that elderly increase their daily physical activity. Regular physical activity is proven to reduce the degree of hypertension.